The sensitivity of human fibroblasts to N-acetoxy-2-acetylaminofluorene is determined by the extent of transcription-coupled repair, and/or their capability to counteract RNA synthesis inhibition. - van Oosterwijk, M F (1996)
Nucleotide excision repair (NER) mechanism is the major pathway responsible for the removal of a large variety of bulky lesions from the genome. Two different NER subpathways have been identified, i.e. the transcription-coupled and the global genome repair pathways. For DNA-damage induced by ultraviolet light both transcription-coupled repair and global genome repair are essential to confer resistance to cytotoxic effects. To gain further insight into the contribution of NER subpathways in the repair of bulky lesions and in their prevention of biological effects we measured the rate of repair of dG-C8-AF in active and inactive genes in normal human cells, XP-C cells (only transcription-coupled repair) and XP-A cells (completely NER-deficient) exposed to NA-AAF. XP-C cells are only slightly more sensitive to NA-AAF than normal cells and, like normal cells, they are able to recover RNA synthesis repressed by the treatment. In contrast, XP-A cells are sensitive to NA-AAF and unable to recover from RNA synthesis inhibition. Repair of dG-C8-AF in the active ADA gene proceeds in a biphasic way and without strand specificity, with a subclass of lesions quickly repaired during the first 8 h after treatment. Repair in the inactive 754 gene occurs more slowly than in the ADA gene. In XP-C cells, repair of dG-C8-AF in the ADA gene is confined to the transcribed strand and occurs at about half the rate of repair seen in normal cells. Repair in the inactive 754 gene in XP-C cells is virtually absent. Consistent with these results we found that repair replication in XP-C is drastically reduced when compared with normal cells and abolished by alpha-amanitin indicating that the repair in XP-C cells is mediated by transcription-coupled repair only. Our data suggest that dG-C8-AF is a target for transcription-coupled repair and that this repair pathway is the main pathway or recovery of RNA synthesis inhibition conferring resistance to cytotoxic effects of NA-AAF. In spite of this, repair of dG-C8-AF in active genes in normal cells by transcription-coupled repair and global genome repair is not additive, but dominated by global genome repair. This indicates that the subset of lesions which are capable of stalling RNA polymerase II, and are, therefore, a substrate for TCR, are also the lesions which are very efficiently recognized by the global genome repair system.